2015
DOI: 10.3390/ijms161024873
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity and in Vivo Toxicity of Double-Point Modified Analogs of 1,25-Dihydroxyergocalciferol

Abstract: Analogs of 1,25-dihydroxyergocalciferol, modified in the side-chain and in the A-ring, were tested for their antiproliferative activity against a series of human cancer cell lines in vitro and in vivo toxicity. The proliferation inhibition caused by the analogs was higher than that of the parent compounds, while the toxicity, measured as the serum calcium level, was lower. All analogs were able to induce, in HL-60 and MV4-11 leukemic cells, G0/G1 cell cycle arrest and differentiation expressed as morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…Many studies have reported that the biological activities of 1,25(OH) 2 D 2 and 1,25(OH) 2 D 3 are very similar [ 45 ]. By contrast, the human malignant melanoma cell lines A375 and SK-MEL 188b, investigated in this study responded differently to the treatment with 1,25(OH) 2 D 3 and 1,25(OH) 2 D 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that the biological activities of 1,25(OH) 2 D 2 and 1,25(OH) 2 D 3 are very similar [ 45 ]. By contrast, the human malignant melanoma cell lines A375 and SK-MEL 188b, investigated in this study responded differently to the treatment with 1,25(OH) 2 D 3 and 1,25(OH) 2 D 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have investigated the activities of low calcemic analogs of vitamin D 3 with 20-hydroxyl, as well as analogs with a short side chain ([ 41 , 42 ], also see [ 40 , 43 ] for recent reviews). In our continuous search for more active vitamin D analogs for use as potential therapeutics [ 44 ], we have investigated the analogs of 1,25-dihydroxyvitamin D 2 (1,25(OH) 2 D 2 ) [ 45 ]. Following the discovery [ 46 ] of an ample free space around the terminal part of the side-chain we designed [ 47 ], synthesized [ 48 ] and investigated the biological activity of side-chain homologated analogs [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that PRI-1906 and PRI-1907, the 1,25D2 analogs with extended and rigidified side-chains, exhibit increased anti-leukemia potency, as compared to 1,25D3 [ 27 , 30 ]. While PRI-1906 is substantially less calcemic than 1,25D3, the much stronger differentiation inducer PRI-1907 is also much more toxic [ 37 , 38 ]. To improve these lead compounds, we recently introduced the 19- nor modification of the A-ring of PRI-1906, resulting in PRI-5201 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diluted solution of 5-FU was added to cell culture at a final concentration of 6 μg/mL (46 μM). 1,25D3, 1,25D2, PRI-2191 [(24 R )-1,24-dihydroxyvitamin D 3 , tacalcitol], PRI-1906, PRI-1907, PRI-1916, and PRI-1917 were synthesized at the Pharmaceutical Research Institute, Warsaw, Poland [ 62 , 63 , 64 , 65 ]. Samples of analogues were aliquoted to amber ampoules and dried down in a stream of argon.…”
Section: Methodsmentioning
confidence: 99%